The Effect of Dewandaru (Eugenia uniflora L.) Fruits Extracts on Testes Heat-induced Rats - Ika Widi Astuti (Journal of Global Pharma Technology, 2019)
Background: Spermatogenesis can run optimally if the testes temperature is 2-8o C lower than body temperature. Higher testicular temperature causes oxidative stress, which results in infertility. The purple-red colour of Dewandaru (Eugenia uniflora L.) fruits have very high of flavonoid. The study aimed to examine the effect of Dewandaru (Eugenia uniflora L.) fruit extract on testis in heat-induced rats. Methods: The study was conducted at Integrated Biomedical Laboratory, Faculty of Medicine, Universitas Udayana between March until July 2019. This True experimental with randomised post-test only control group design consisted of a total of 24 rats. These were divided into four groups, with the group I and II was a negative and positive control. Group III and IV were treatment pre and post heat induction. Lipid peroxidation (MDA) level, Bcl-2, serum testosterone, and testis weight were measured. Data were presented as mean, and one-way ANOVA was used as a statistical tool with significant p<0.05. Result: Treatment with Dewandaru (Eugenia uniflora L.) fruit extract before and after heat induction, respectively showed a decrease significantly in the serum lipid peroxidase level, increase in the Bcl-2 expression, testosterone level, and testis weight. There is no significant difference between treatment pre and post heat induction. Conclusion: This study shows that Dewandaru (Eugenia uniflora L.) fruit extract altered the lipid peroxidase level, Bcl-2, testosterone level, and testis weight.Keywords: Bcl-2, Dewandaru fruits extract, Heat induction, MDA, Oxidative stress, Testosterone, Testis weight.